Game-Based Learning Models on Increasing Creativity and Learning Outcomes of Elementary School Students - Eges Triwahyuni; Rina Ika Wahyunigtyas (Universitas Pendidikan Ganesha, 2025)
Field evidence indicates low student creativity and learning outcomes due to difficulties in understanding the material, influenced by the dominance of conventional teaching models in elementary schools. The aim was to examine the effect of the Game-Based Learning (GBL) model on improving creativity and learning outcomes in elementary school students. This study used a quantitative approach with a quasi-experimental (non-equivalent control group) design. The subjects consisted of 28 fourth-grade students divided into two groups: an experimental group and a control group. The experimental group received GBL-based learning, while the control group received conventional learning. Data were collected through pretests and posttests using validated learning outcome test instruments and a creativity questionnaire. Data analysis was performed using normality tests and independent sample t-tests. The results showed that the GBL model significantly improved student creativity and learning outcomes. The N-Gain score in the experimental group was higher than in the control group, with a very large effect size (Cohen's d > 8). Specifically, creativity indicators such as fluency, originality, and elaboration experienced significant improvements. Learning outcomes also improved in cognitive aspects. It can be concluded that the GBL model has proven effective in creating enjoyable, challenging, and pedagogically meaningful learning experiences. This study recommends the use of GBL as an alternative learning strategy that can develop students' creative potential or creative thinking while simultaneously improving elementary school students' academic achievement.